Preparation, Physicochemical Properties and Stability of Anthocyanin Nanoliposomes Before and After Double-Layer Modification Using Synanthrin and Pea Protein Isolate - Lianlian Zhang; Aniya; Shengping Xing; Jing Li; Ying Liu; Chaozhi Li; Jianhang Zhu; Yan Li; Xiaoji Fu (Molecules)
Anthocyanins (ACNs), characterized by their polyhydroxy structures, exhibit high susceptibility to external environmental factors, which significantly limits their application in the food and industrial sectors. To enhance the stability of anthocyanins, anthocyanin nanoliposomes (ACN-NLs) were developed, with encapsulation efficiency, particle size and zeta potential serving as key evaluation parameters. Furthermore, through layer-by-layer self-assembly and electrostatic interactions, ACN-NLs were modified using synanthrin (SY) and pea protein isolate (PPI). Consequently, PPI-modified ACN-NLs (PPI-ACN-NLs) and SY-PPI-modified ACN-NLs (SY-PPI-ACN-NLs) were successfully synthesized. In this study, the structural characteristics of liposomes were investigated using X-ray diffraction (XRD), their in vitro digestibility was evaluated, and their stability under different temperatures, light conditions, and simulated food system conditions was assessed. The results demonstrated that when the mass ratio of soybean lecithin to cholesterol, soybean lecithin to anhydrous ethanol, and drug-to-lipid ratio were set at 5:1, 3:100, and 3:10, respectively, with an ACN concentration of 4 mg/mL, a pea protein solution with pH 3.0, a PPI concentration of 10 mg/mL, and an SY concentration of 8 mg/mL, the prepared ACN-NLs, PPI-ACN-NLs, and SY-PPI-ACN-NLs exhibited optimal performance. Their respective encapsulation efficiencies were 52.59 ± 0.24%, 83.80 ± 0.43%, and 90.38 ± 0.24%; average particle sizes were 134.60 ± 0.76 nm, 213.20 ± 0.41 nm, and 246.60 ± 0.24 nm zeta potentials were −32.4 ± 0.75 mV, −27.46 ± 0.69 mV, and −16.93 ± 0.31 mV. The changes in peak shape observed via X-ray diffraction (XRD), in vitro digestion profiles, and alterations in anthocyanin release rates under different conditions collectively indicated that the modification of ACN-NLs using SY and PPI enhanced the protective effect on the ACNs, improving their biological activity, and providing a robust foundation for the practical application of ACNs.